THE RELATIONSHIP BETWEEN FAMILY INCOME AND THE NUTRITIONAL STATUS OF PREGNANT MOTHERS AT AMPEL 1 PRIMARY HEALTH CARE CENTER IN BOYOLALI REGENCY - Rahayu, Kurnia; Rahmawati, Alfiah; Susiloningtyas, Is (Transpublika Publisher, 2023)
Pregnancy represents a significant phase in the lives of women, particularly for those who are married. Thus, pregnancy necessitates specialized attention, especially concerning the fulfillment of energy and nutritional requirements. The quality of maternal dietary intake before and during pregnancy has the potential to influence the health of both the mother and her baby. Malnutrition during pregnancy can lead to various complications, affecting both the mother and the fetus, including issues like anemia, bleeding, and inadequate maternal weight gain. Maternal nutritional intake is influenced by a multitude of internal and external factors within the pregnant mother and her family, encompassing factors such as low levels of knowledge, social dynamics, and household income. This study aims to explore the correlation between the nutritional status of pregnant women and the family income level at the Ampel Health Center in Boyolali Regency. The research employs a quantitative approach utilizing an analytical survey method with a cross-sectional design. The study involved a sample size of 30 pregnant women. The results reveal that the majority of participants are aged between 20-35 years, predominantly in the second trimester of pregnancy, with 10 respondents (33.3%) in trimester II and 20 respondents (66.6%) in trimester III. The Spearman's rank correlation test yielded a p-value of 0.353, which is above the significance level of 0.05 (0.353 > 0.05). Nonetheless, there is no significant correlation between the nutritional status of pregnant women and the family income level at the Ampel Health Center in Boyolali Regency.